The K-popification of Anies Baswedan: Exploring fandom culture and youth involvement in Indonesia's 2024 election - Putri, Salsa Della Guitara; Purwaningsih, Titin (ARISTO, 2026)
The 2024 Indonesian presidential election marked a significant shift in political engagement, particularly among young voters, who leveraged digital platforms and fandom culture to promote their preferred candidates. This study explores the K-popification of Anies Baswedan’s campaign, a phenomenon where youth-driven political participation mirrored K-pop fandom dynamics, transforming traditional electoral strategies. By utilizing Philip Niffenegger’s 4P Model of Political Marketing which involved Product, Promotion, Price, and Place, this research examines how Anies Baswedan's campaign evolved into a fan-centric movement that increased visibility, engagement, and voter mobilization. The study employs a qualitative case study approach, analyzing social media content, grassroots initiatives, and digital activism strategies that framed Anies Baswedan as an "idol-like" figure. Findings suggest that youth engagement in political campaigns is shifting from passive participation to interactive, community-driven movements, facilitated by social media’s algorithmic power. This research contributes to the growing discourse on political marketing, fandom activism, and digital youth mobilization, highlighting the blurring boundaries between entertainment culture and electoral politics. However, the phenomenon appears largely confined to younger, digitally active demographics and may not resonate with older or rural populations who are less engaged in online platforms. Future studies should explore the potential of translating such digital movements into broader, offline civic engagement to assess their long-term impact and inclusivity.